Multidimensional differences of right- and left-sided colorectal cancer and their impact on targeted therapies - Marwa Abdel Hamid; Lorenz M. Pammer; Silvia Oberparleiter; Michael Günther; Arno Amann; Rebecca A. Gruber; Anna Mair; Fabienne I. Nocera; Steffen Ormanns; Kai Zimmer; Romana R. Gerner; Florian Kocher; et al. (npj Precision Oncology)
Abstract Despite advances in metastatic colorectal cancer (mCRC) treatment, long-term survival remains poor, particularly in right-sided colorectal cancer (RCRC), which has a worse prognosis compared to left-sided CRC (LCRC). This disparity is driven by the complex biological diversity of these malignancies. RCRC and LCRC differ not only in clinical presentation and outcomes but also in their underlying molecular and genetic profiles. This article offers a detailed literature review focusing on the distinctions between RCRC and LCRC. We explore key differences across embryology, anatomy, pathology, omics, and the tumor microenvironment (TME), providing insights into how these factors contribute to prognosis and therapeutic responses. Furthermore, we examine the therapeutic implications of these differences, considering whether the conventional classification of CRC into right- and left-sided forms should be refined. Recent molecular findings suggest that this binary classification may overlook critical biological complexities. Therefore, we propose that future approaches should integrate molecular insights to better guide personalized treatments, especially anti-EGFR therapies, and improve patient outcomes.